TEKNOLOGI PENGOLAHAN DAN PEMANFAATAN KARBON AKTIF UNTUK INDUSTRI - Effendi Arsad; Saibatul Hamdi (Kementerian Perindustrian, 2010)
The activated carbon is very important for has processed product activated carbon. In south Kalimantan has a big prospects due to the big potential of the raw material provided by the nature and industrial waste. There are a lot of raw materials that can be used for the manufacture of activated carbon such as agricultural waste, sugarcane waste, waste of sawn timber, lives stock waste and coal processing waste.Manufacture of activated carbon can be done in ways: chemical and physical processes. Activation is very important in the manufacture of activated carbon in addition to the raw materials used. Activated carbon is charcoal that has undergone changes in chemical properties and physical properties due to be activated with the activator chemical materials or can by heating at high temperatures, so that absorption , surface area, and the ability to absorb become as very good. Activated carbon is used as an absorbent to absorb heavy metals, in medicine and food, on liquor, petroleum chemical, shrimp farming, the sugar industry of gas purification, catalyst and fertilizer processing.Key wood : technology processed, activated carbon